Psychometric properties of the Eating Disorder Examination‐Questionnaire and psychopathology in Japanese patients with eating disorders. Issue 2 (23rd December 2020) - Otani, Makoto; Hiraide, Maiko; Horie, Takeshi; Mitsui, Tomoyo; Yoshida, Toshiyuki; Takamiya, Shizuo; Sakuta, Ryoichi; Usami, Masahide; Komaki, Gen; Yoshiuchi, Kazuhiro
Abstract: Objective: The Eating Disorder Examination‐Questionnaire (EDE‐Q) is one of the most widely used tools to assess the core psychopathology of eating disorders (ED). However, recent empirical findings did not support the original four‐factor structure. The aims of the present study were to investigate the factor structure of the EDE‐Q in Japanese ED patients, to test the reliability and convergent validity of the EDE‐Q, to examine group differences between various ED groups and healthy participants, and to explore the main behavioral features of Japanese ED patients using the newly developed Japanese version of EDE‐Q. Method: A total of 148 ED patients and 469 healthy participants completed the EDE‐Q, Eating Attitudes Test‐26 (EAT‐26), and Eating Disorder Inventory‐2 (EDI‐2). The factor structure, reliability, and validity of the EDE‐Q were assessed in ED patients. Group differences were assessed using the new Japanese version of the EDE‐Q (EDE‐Q‐J). Results: The EDE‐Q‐J had three factors. Cronbach's alphas ranged from 0.83 to 0.93. Total score and subscale scores of "Dieting" and "Bulimia and Food Preoccupation" of EAT‐26 and of "Drive for Thinness, " "Body Dissatisfaction, " and "Bulimia" of EDI‐2 correlated with the global score and three subscale scores of the EDE‐Q‐J. Discussion: For Japanese female ED patients, the EDE‐Q‐J had three subscales that were not consistent with the original subscales, but were interpretable. It demonstrated sufficient reliability and validity. Japanese female patients with restricting‐type anorexia nervosa (AN‐R) displayed less dissatisfaction with shape and weight than healthy participants. AN‐R patients in Japan might present with a non‐fat‐phobic symptom profile.